(untitled) (Malaysian Journal of Civil Engineering, 2018)
The recent earthquakes in India and different parts of the world have caused loss of human lives and damage to property due to the collapse of structures. Though an earthquake cannot be prevented, the loss of life and property can be minimized by taking necessary steps on the existing structures to reduce the damages. The seismic codes contain provisions for planning and designing earthquake resistant structures. It becomes essential to carry out a survey and identify existing structures that are deficient and carry out appropriate retrofit. This study first identifies the earthquake resistant features stipulated by the seismic codes for buildings. Then a survey assessment carried in the district of Kollam (Kerala, India) is reported. Kollam is in moderate seismic risk zone, in the seismic zone map prepared by the Bureau of Indian Standards. This city deserves attention owing to high concentrations of population. Each area differs from one another in terms of climate, culture, methods of construction and living standards. Materials used for construction also differ. The localized survey has found out the methods of construction, materials used for construction and general pattern of the structures in Kollam city. Structures that are prone to damage during a seismic event were identified. Recommendations are given based on the guidance available in seismic codes and other references for retrofitting such structures.